2006
DOI: 10.1017/s0033291706009184
|View full text |Cite
|
Sign up to set email alerts
|

Emotional bias and waking salivary cortisol in relatives of patients with major depression

Abstract: Subtle biases in the processing of emotional information may exist in the unaffected first-degree relatives of those with depression. As such, this may represent a familial vulnerability factor to developing a depressive illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…11 However, the pathophysiology of the role that family history of MDD plays in the development and diagnosis of MDD is not yet entirely understood. The behavioural data suggest that the key skills impaired in individuals with a family history of MDD are emotion processing [12][13][14] and attention shifting from emotional content, 15,16 neural correlates of which have been previously verified in healthy individuals. [17][18][19] These 2 processes are crucial components of emotional regulation 20,21 and represent its 2 basic functions: an ability to explore emotional meaning of the environment and a potential to withdraw from the exploration in accordance with one's goals.…”
Section: Introductionmentioning
confidence: 57%
“…11 However, the pathophysiology of the role that family history of MDD plays in the development and diagnosis of MDD is not yet entirely understood. The behavioural data suggest that the key skills impaired in individuals with a family history of MDD are emotion processing [12][13][14] and attention shifting from emotional content, 15,16 neural correlates of which have been previously verified in healthy individuals. [17][18][19] These 2 processes are crucial components of emotional regulation 20,21 and represent its 2 basic functions: an ability to explore emotional meaning of the environment and a potential to withdraw from the exploration in accordance with one's goals.…”
Section: Introductionmentioning
confidence: 57%
“…Bouhuys et al [1999] found that increased perception of negative emotions is related to relapse, although the recognition of negative emotions decreased from the acute to the remitted phase. The conceptualization of fear recognition as a vulnerability marker was further supported in a study by Masurier et al [2007], who found faster recognition of facial expressions of fear in female first-degree relatives of depressed patients compared to controls without a family history of depression. Biases in the processing of emotional information may thus be a stable trait characteristic, even occurring before the onset of a first depressive episode [Leppänen, 2006;review].…”
Section: Discussionmentioning
confidence: 91%
“…For conscious tasks, high-risk individuals with subclinical depressive symptoms have been reported as being less accurate [36] and quicker [37] at identifying negative and neutral emotions, and other research shows them to be less accurate in identifying happiness. [38] Misidentification rates show that highrisk individuals also have a greater tendency to perceive negative emotion.…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al [38] NEUROTICISM (N): EPQ [101] High N: 33 (22), 18.82(0.98) EPQ 9.58 (8)(9)(10)(11)(12); BDI [88] 8.33 (5.97) Low N: 42 (18) Csukly et al [36] DEPRESSIVE SYMPTOMS: Thirteen depression items from SCL-90 [102] Healthy participants: 117 (68) [37] FIRST DEGREE RELATIVES of patients with depression: FH-RDC [103] Relatives: 25(25), 39.8(13.9) BDI [88] 3.8(4.4); EPQNeuroticism [101] 6.8(3.7)…”
mentioning
confidence: 99%